1967
DOI: 10.6028/jres.071a.028
|View full text |Cite
|
Sign up to set email alerts
|

The dissociation constants of some disubstituted anilines and phenols in aqueous solution at 25 C

Abstract: Th e di ssoc ia ti on co nsta nts of s ix di s ub stituted a nilin es and of fiv e di s ub s titut ed ph e nols in a qu eo us so lution a t 25°C hav e bee n meas ured u sin g th e s pec troph otome tri c method. Co nsid era tio n is give n to th e ex t ent to whi c h these di ssoc iati o n co nstants can be predicted from co rrespo ndin g values for monos ub s titut e d anil in es and Dh en ols . In additi on , th e qu esti on as to wh e th e r th e pK value of a su b· stituted anil ine c an be pred icted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The observed pKa value of 4.46 for DNOC was in very good agreement with that (pKa = 4.47) determined spectrophotometrically by Robinson (1967a), whereas the observed p7fa value (4.62) for dinoseb differed from that (4.40) reported by Weber (1972). The o-bromo (-7, + 7) substituents (2,6-dibromophenol; pKa = 6.69; Robinson, 1967b) and p-cyano (-/, -AT) group (p-cyanophenol; pffa = 7.97; Fickling et al., 1959) of bromoxynil and the chloro (-7, +M) substituents (2,4,6trichlorophenol; pKa = 6.23; Fischer et al, 1967;3,5-dichlorophenol; pKa = 8.18; Robinson, 1964) of pentachlorophenol are acid strengthening. There was some difference between the observed plfa value (4.20) for bromoxynil and that (4.08) reported by Weber (1972), whereas the observed plfa value (4.71) for pentachlorophenol compared well with the spectrophotometrically determined value (4.74) of Drahonovsky et al (1971).…”
Section: Methodsmentioning
confidence: 99%
“…The observed pKa value of 4.46 for DNOC was in very good agreement with that (pKa = 4.47) determined spectrophotometrically by Robinson (1967a), whereas the observed p7fa value (4.62) for dinoseb differed from that (4.40) reported by Weber (1972). The o-bromo (-7, + 7) substituents (2,6-dibromophenol; pKa = 6.69; Robinson, 1967b) and p-cyano (-/, -AT) group (p-cyanophenol; pffa = 7.97; Fickling et al., 1959) of bromoxynil and the chloro (-7, +M) substituents (2,4,6trichlorophenol; pKa = 6.23; Fischer et al, 1967;3,5-dichlorophenol; pKa = 8.18; Robinson, 1964) of pentachlorophenol are acid strengthening. There was some difference between the observed plfa value (4.20) for bromoxynil and that (4.08) reported by Weber (1972), whereas the observed plfa value (4.71) for pentachlorophenol compared well with the spectrophotometrically determined value (4.74) of Drahonovsky et al (1971).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the molecular properties and the electrodynamical behavior are conditioned by the pH of the solution (through the formation of anionic, zwitterionic, or cationic species) and by the charge of the metal surfaces. Thus, because (1) the probability of a large contribution from binuclear molecules, azobenzene, and hydrazobenzene in alkaline and neutral solutions and (2) the p K values of most substituted anilines and nitrobenzenes are less than 3, it was preferable to perform measurements in acidic solutions, in which m -NO 2 PhG(cHex)P and m -NO 2 PhG(Morf)P are neutral but m -NO 2 PhG(An)P is present as the anilinium cation. Additionally, in most cases, it was observed that the aromatic nitro molecules are subjected to photoreduction (NO 2 → NH 2 ) on the silver surface .…”
Section: Resultsmentioning
confidence: 99%